Karyomegalic interstitial nephritis: diagnosed only when suspected - Monica Sivakumar; Balan Louis Gaspar; Balakrishnan Narasimhan (BMC, 2021)
Abstract Background Karyomegalic interstitial nephritis (KIN) is an uncommon cause of chronic interstitial nephritis that eventually progresses to end-stage renal disease. Overall less than 50 cases have been reported in the literature. Case presentation We describe an asymptomatic 25-year-old gentleman with a family history of chronic interstitial nephritis who came to check the status of his kidney functions. On evaluation, he was found to have chronic interstitial nephritis which could not be attributed to a specific etiology. Renal biopsy confirmed the diagnosis of KIN. Conclusion KIN remains underdiagnosed. It is important to recognize this entity because of the familial nature, a wide range of differential diagnoses, and prognostic implications. A high index of clinical suspicion is necessary to perform renal biopsy which remains the gold standard for the diagnosis of KIN.